â€œTHE SHAWLâ€, THE SUBALTERN, AND THE CASE OF THE SUBALTERN GENOCIDE - Gultom, Natan (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2019)
Holocaust studies post-World War II have found ways in intersecting to other studies within the Postmodern era. In 1980, a short-story â€œThe Shawlâ€ was written depicting a holocaust brutality done towards the Jews. The story revolves around a Jewish woman, Rosa, that lived through the bitterness of seeing her daughter, Magda, being slaughtered in a concentration camp. In the context of â€œThe Shawlâ€, this article would like to describe the relationship between holocaust studies and the subaltern studies within postcolonialism. Furthermore, this article discusses if there are hints â€œThe Shawlâ€ invokes a sentiment for the Jews to take revenge towards their former oppressors. The aim of this article is to further the argument â€œThe Shawlâ€ has no characteristics of taking revenge which eventually leads to subaltern genocide. â€œThe Shawlâ€ functions better as a remembrance so generations of the future do not repeat the horrors of the past.